Preemptive Kidney Transplantation Is Associated With Transplantation Outcomes in Children: Results From the French Kidney Replacement Therapy Registry. Issue 2 (February 2022) - Prezelin-Reydit, Mathilde; Madden, Iona; Macher, Marie-Alice; Salomon, Rémi; Sellier-Leclerc, Anne-Laure; Roussey, Gwenaelle; Lahoche, Annie; Garaix, Florentine; Decramer, Stéphane; Ulinski, Tim; Fila, Marc; Dunand, Olivier; et al.
Abstract : Background: Kidney transplantation (KT) is the optimal treatment for children with end-stage kidney disease. The aim of this study was to evaluate the impact of preemptive kidney transplantation (PKT) and of pretransplant dialysis duration on graft survival among French pediatric kidney transplant recipients. Methods: We analyzed all first pediatric kidney-only transplantations performed in France between 1993 and 2012. A Cox multivariable model was used to investigate the association of PKT and pretransplant dialysis time with the hazard of graft failure defined as death, return to dialysis, or retransplant, whichever occurred first. Results: Patients (n = 1911) were included, of which 380 (19.8%) received a PKT. Median time of follow-up was 7.0 y. PKT was associated with a 55% reduction of the hazard of graft failure at any time after KT compared with patients transplanted after dialysis (hazard ratio, 0.45; 95% confidence interval, 0.33-0.62), after adjustment for recipient sex and age, primary kidney disease, donor age and type (living or deceased donor), number of HLA mismatches, cold ischemia time, and year of transplantation. A reduction of the hazard of graft failure was found in PKT whatever the compared duration of dialysis, even when <6 mo and whatever the dialysis modality. Results were similar in multiple sensitivity analyses. Conclusions: In France, PKT among pediatric patients is associated with a better graft survival when compared with KT after dialysis, even when <6 mo. Based on these findings, we suggest that PKT should be considered as the treatment of choice for children with end-stage kidney disease. Abstract : Supplemental Digital Content is available in the text.